Union formation patterns of moroccans in Spain - Esteve Palós, Albert; Jiménez Pérez, Edurne (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
This paper explores the marriage patterns of Moroccans in Spain. First, we examine the factors that affect the likelihood of having a partner and/or co-resident partner in Spain and, among those who have a partner, the factors associated with being married to a non-Moroccan spouse (intermarriage). Starting from the 2001 Spanish sample of Census microdata (n = 8.934) we apply multilevel logistic regression models for binary responses to estimate the effect of the independent variables. At a regional level, we use the size of the group and the sex ratio and, at individual level, we use years in the country and educational attainment. Results show that disequilibria in the marriage market do not have impact on union formation patterns among Moroccans in Spain, which clearly suggests the binational character of the Moroccan marriage market. At the individual level, years of stay and educational attainment are positively related to intermarriage either among women or men. For men, educational attainment is positively correlated to the fact of living with the partner in Spain. By contrast, highly educated women are less likely to be in union. Higher education challenges traditional marriage patterns for Moroccan women
Keywords: Morocco; Spain; Marriage; Intermarriage